A study on the effect of husbands\' attendance in the delivery ward on the duration of labor and mode of delivery in primigravid women - Nahid Haji Hoseini; Narjes Sadat Borghei; Mitra Reyhani; Mahin Tatari (Golestan University of Medical Sciences, 2023)
Background: Husband attendance during labor provides psychological support for her, and may also affect the duration of childbirth. Therefore, the present study was conducted to investigate the effect of the husband attendance in delivery ward on duration of labor and mode of delivery of primigravid women. Methods: The present study is a field trial study that was performed on 57 couple in Kalaleh hospital in 2021 of primigravid women. The samples were assigned to two groups using a quadratic block method. The intervention group husbands attended beside their wife for at least two hours during active phase and control group received routine care. Data were collected using information form and checklist and analyzed using Mann-Whitney, Chi-square and Fisher's exact test. Results: The mean of husband attendance during labor in minute was 152.32±32.25 in the intervention group. The mean of active phase in minute was 279.43±169.78 in the intervention and 345.69±167.94 in the control groups, despite the difference of 66.26 minutes in the averages, it was not statistically significant (p>0.05). In addition, there was no significant difference in the mode of delivery in the two groups. Conclusion: There was no difference in the duration and mode of delivery in the two groups under investigation, thus 2 hours husbands' attendance in delivery ward did not affect time and mode of delivery.